Gambaran Kualitas Hidup Penderita Penyakit Jantung Koroner Pasca Serangan Jantung - Basuki Rahmat; Seto Priyambodo; Dian Puspita Sari; Yoga Pamungkas Susani; AASG Mas Meiswaryasti Putra (Faculty of Medicine Universitas Mataram, 2020)
Background: Patients suffering from coronary heart disease can experience psychological changes as well as quality of life. This study aims to determine the quality of life of patients with coronary heart disease post heart attack. Methods: A total of 30 patients with coronary heart disease after diagnosed STEMI, NSTEMI, or unstable angina for less than one year and had never been diagnosed with a mental disorder. Quality of life was measured by the Indonesian version of the SF-36 Health Survey instrument. Unpaired t-test and Mann Whitney test was conducted to analyze the differences the quality of life based on gender. Results: As many as 36.7% of subjects stated that the current condition was somewhat worse than one year ago. Subjects who stated the same or better were 56.6%. Men have a higher quality of life than women, although it is not statistically significant (p> 0.05). Emotional well-being is the dimension that has the highest average (75.1 ± 17.3) in both the male group (74.8 ± 17.7) and the female group (77.3 ± 16.7). Role limitations due to emotional problems have the lowest score (18.8 ± 33.5) followed by role limitations due to physical problems (20.0 ± 29.7). Conclusion: Patients with coronary heart disease after the attack have the perception that there are limited roles both due to emotional and physical problems. There was no significant difference between the quality of life of coronary heart disease sufferers after the attack of the male and female groups.